Subcritical water extraction (SWE) and ultrasonic-assisted extraction (UAE) of bioactive compounds from Morinda citrifolia: comparative evaluation of process efficiency - Husna Abdul Somat,; Intan Safura Saipul Anwar,; Wan Aida Wan Mustapha,; Siti Mazlina Mustapa Kamal,; Nurfatimah Mohd Thani, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Morinda citrifolia has garnered significant interest from researchers in the food and pharmaceutical industries. Despite this interest, research on extracting its beneficial components using green technologies remains limited. This study aims to investigate the effect of two extraction techniques namely subcritical water extraction (SWE) and ultrasonic-assisted extraction (UAE) on the total phenolics content and antioxidant activity of M. citrifolia leaf extracts using response surface methodology (RSM). A three-level factorial central composite design (CCD) was applied to determine the effect of three independent variables for each method of UAE (X1: citric acid concentration, X2: extraction time, X3: ultrasonic amplitude) and SWE (X1: operating temperature, X2: extraction time, X3: solid loading) on three dependent variables (Y1: total phenolic content (TPC), Y2: free-radical scavenging activity (DPPH), Y3: ferric reducing antioxidant activity (FRAP)). The optimum value of TPC and DPPH by UAE are 48.25 mg GAE/g and 22.59% inhibition, respectively, which are lower than the optimal values obtained by SWE method, with respective values of 64.96 mg GAE/g and 80.75% inhibition. However, the FRAP value possessed by UAE was higher compared to SWE, with respective values of 29.63 mg GAE/g and 11.33 mg GAE/g. The results indicate that extraction temperature (p<0.05) was the most significant factor that enhances phenolic yield and antioxidant activity in MC leaves using SWE, while citric acid concentration notably influences UAE extracts the most. The UAE demonstrated higher process efficiency compared to SWE. However, due to the use of samples with significantly different sizes in the evaluation, further analysis is needed to make a definitive comparison of process efficiency between the two methods.